DEMONSTRASI PEMBUATAN SUSU KACANG HIJAU SEBAGAI PENCEGAHAN STUNTING DI DESA NGAMPELREJO KECAMATAN JOMBANG KABUPATEN JEMBER - Saputra, Harmawan Teguh; Aryatno, Risqi Pradana; Zahro, Shofiatus; Saputra, Rehanuddin Aji; Mursida, Siti (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is a chronic nutritional problem that results in impaired growth in toddlers, which can have a negative impact on the child's physical and cognitive development. Jember Regency has a fairly high prevalence of stunting, including in Ngampelrejo Village. This community service program aims to educate mothers of kindergarten and PAUD students in Ngampelrejo Village about preventing stunting through a demonstration of making green bean milk, which is known to be rich in nutrients. This activity was carried out in three stages: socialization about stunting, socialization about the nutritional value and benefits of green beans, and practical training in making green bean milk. The methods used included lectures, interactive discussions, direct demonstrations, and active participant participation. The evaluation results showed that the participants had a good understanding of stunting and the benefits of green beans, with the average assessment scores were 8 and 9 respectively. In the skill of making green bean milk, participants showed adequate ability with a score of 8. The participants also showed high involvement in the discussion and considered the knowledge gained easy to apply at home, with an average score of 9. This program succeeded in increasing the understanding and skills of mothers in preventing stunting by processing green beans into nutritious milk. Thus, this training is expected to be an effective model to be implemented in other villages with similar problems, so that it can help reduce stunting rates and improve the quality of life of children in Jember Regency.